A Second Order IMEX Method for Radiation Hydrodynamics. (July 2020) - Zhao, Yang
Abstract: Radiation hydrodynamics problem is mulitphysics field coupled and challenge in mathematics. A new scheme, IMEX, is put forward in solving RHD equations when the explicit method have an extremely small time step and implicit method have a complicated and high cost solver. RHD equations are solving by splitting the explicit operator and implicit operator with IMEX scheme. The results of Riemann problems are plotted and the scheme shows the effect to lower the computation cost.